Subjectivity and Mother-Daughter Relationship in Frog Under a Coconut Shell Novel by Josephine Chia - Novia Nurul Ulfah; Aquarini Priyatna; Amaliatun Saleha (Universitas Negeri Semarang, 2024)
This research discusses how the subjectivity and mother-daughter relationship are depicted in the autobiographical novel Frog under a Coconut Shell (2002) by Josephine Chia, a writer from Singapore. This autobiography tells the story of the daughter’s relationship with her mother, which was based on a patriarchal cultural environment and challenging economic conditions. The novel's relationship between mother and daughter shows the ambivalence regarding the constructed female subjectivity. This research aims to show how the mother’s subjectivity in the autobiography is built through the relationship of the mother and daughter, which is presented through narrative descriptions and dialogue. This research uses a qualitative method with an autobiographical narrative approach based on the theory of motherhood and mothering, especially regarding the relationship between mother and daughter. The results of this research show that the subjectivity of the mother character builds relationships with her daughter. This relationship shapes the daughter’s life by manifesting the mother’s hopes for her daughter. However, this subjectivity must still obey patriarchy to make the hopes can be realized. In addition, this autobiography also shows that the mother’s function as a fulfiller of needs also applies to a daughter who fulfills the mother’s needs. Based on the findings in this research, it is expected that it can be a reflection that the relationship between mother and daughter can be a source of subjectivity for both sides.